Questions in Trial in District Court (Cyanide Coffee Case) - Jumiati, Resa; Setiawan, Teguh (Master Program in Linguistics, Diponegoro University, 2025)
This study aims to explore the types and objectives of questions in the trial of cyanide coffee cases. The method used is qualitative descriptive. The source of research data is the trial conversation of Jessica Wongso's case in the form of video recordings from the Kompas TV YouTube channel. The research corpus was drawn from four trial videos asked in 2016. Data was collected by observation techniques and recording techniques. The research instrument is a human instrument. The transcribed data was analyzed using matching and distribution data analysis techniques. The validity of the data is carried out by theoretical triangulation. Based on the results of the research, two conclusions can be drawn. First, 1585 data consisting of four types of questions were found. The four types of questions include 543 or 34.3% declarative questions, 501 or 31.66% wh questions, 397 or 25% polar questions, and 144 or 9.1% disjunctive questions. Second, when viewed by objective, these types of questions consist of three objectives, namely 713 or 45% of questions constructed for confirmation purposes, 603 or 38.1% of questions aimed at obtaining information, and 267 or 16.9% of questions for clarification. Thus, the process of analyzing the data of the question in the trial of the cyanide coffee case is interrelated between the type and purpose of the question.